Low Lymphocyte-to-Monocyte Ratio as a Possible Predictor of an Unfavourable Clinical Outcome in Patients with Acute Ischemic Stroke after Mechanical Thrombectomy - Katarína Pinčáková; Georgi Krastev; Jozef Haring; Miroslav Mako; Viktória Mikulášková; Vladimír Bošák (Stroke Research and Treatment)
Background. Although considerable progress has been made in the treatment of acute ischemic stroke (AIS), the clinical outcome of patients is still significantly influenced by the inflammatory response that follows stroke-induced brain injury. The aim of this study was to evaluate the potential use of complete blood count parameters, including indices and ratios, for predicting the clinical outcome in AIS patients undergoing mechanical thrombectomy (MT). Methods. This single-centre retrospective study is consisted of 179 patients. Patient data including demographic characteristics, risk factors, clinical data, laboratory parameters on admission, and clinical outcome were collected. Based on the clinical outcome assessed at 3 months after MT by the modified Rankin Scale (mRS), patients were divided into two groups: the favourable group (mRS 0–2) and unfavourable group (mRS 3–6). Stepwise multivariate logistic regression analysis was used to detect an independent predictor of the unfavourable clinical outcome. Results. An unfavourable clinical outcome was detected after 3 months in 101 patients (54.4%). Multivariate logistic regression analysis confirmed that the lymphocyte-to-monocyte ratio (LMR) was an independent predictor of unfavourable clinical outcome at 3 months (odds ratio=0.761, 95% confidence interval 0.625–0.928, and P=0.007). The value of 3.27 was chosen to be the optimal cut-off value of LMR. This value could predict the unfavourable clinical outcome with a 74.0% sensitivity and a 54.4% specificity. Conclusion. The LMR at the time of hospital admission is a predictor of an unfavourable clinical outcome at 3 months in AIS patients after MT.